Molecular regulatory events of flower and fruit abscission in horticultural plants - Yuan Shi; Bangqian Song; Qin Liang; Deding Su; Wang Lu; Yudong Liu; Zhengguo Li (Horticultural Plant Journal, 2023)
Flower and fruit abscission is a highly programmed physiological process, which is closely related to the yield of horticultural plants. The coordination of many regulatory factors associated with metabolic and signaling pathways plays a key role in the flower and fruit shedding. Hormones, peptides, carbohydrates, polyamines or cell wall modifying proteins regulate flower and fruit shedding. This article reviewed the recent studies of flower and fruit abscission, including the molecular regulation mechanism of abscission zone formation, typical structure and location of abscission zones, and other factors affecting flower and fruit abscission, such as stresses, hormones, peptides, carbohydrates, polyamines and cell wall modifying proteins. Overall, the review summarizes the developmental mechanism and the diversity of abscission zones, and the key factors affecting flower and fruit abscission of horticultural plants, aiming to provide guidance for studying the molecular regulatory mechanism of flower and fruit abscission.